The improbability of love - Rothschild, Hannah, 1962- (Alfred A. Knopf, 2015)
"Annie McMorrow, 31 and not recovered from the end of her long-term relationship, is an assistant to film producer Carlo Spinetti and then to his chilling wife Rebecca Winkleman Spinetti whose father started Winkleman Fine Art in Curzon St. Annie has spent her meager savings on a dusty painting from a junk shop to give to her new, unsuitable, boyfriend who never shows up for his birthday dinner. The painting now hers, talks, but only to us. Shrewd, spoiled, charming, world weary and cynical, he comments perceptively on Annie, and the modern world and tells tales about his previous owners: Louis XV, Voltaire, Catherine the Great among others."--